A terceirização de serviço de alimentação coletiva em instituições federais de ensino superior: estudo de caso em restaurante universitário - Caran, Dalila Ferraz Lima Ferreira (2018)
The collective diet is part of the market segment of providing ready-to-eat meals to healthy populations. These activities are carried out in the Food and Nutrition Units of the commercial or institutional types. In order to ensure the quality and efficiency of the services provided various organizations choose to outsource these services. University Restaurants of the Federal Institutions of Higher Education are examples of institutional Food and Nutrition Units . Through them, the Federal Institutions of Higher Education perform support and guarantee of maintenance of the National Program of Student Assistance. The Federal Institutions of Higher Education can opt for two types of outsourcing: (1) mixed self-management, through contracting services with supply of jobs with partner companies and acquisition of inputs by the public organization; and (2) concession of use of physical area associated with the provision of catering service, henceforth called total concession, in which case the contracted company is responsible for all stages of the production process. This study aims to evaluate the application of the "total concession" model as alterative for the management of the University Restaurant located in the University Center North of Espírito Santo, comparing it with the current "mixed self-management" model. For this, the study analyzed the practice of the two types of outsourcing of collective feeding services in Federal Institutions of Higher Education in the southeastern region of Brazil. The study comprises: (1) evaluation of the costs involved; (2) analysis of the benefits and deficiencies of each modality in order to better infer the adequacy of the organization's reality, guaranteeing efficiency of the sector and maximizing the use of the public resources involved. The costs and quality standards could be verified through the analysis of the bidding documents and the contracts signed between the public institutions and the outsourced companies contracted for these purposes. The detailed analysis of the documents collected in the documentary research evidenced the adoption of the concession in several universities of the region, performing an average cost of R$ 8.75 (eight reais and seventy five cents) to in the year 2017 and made possible the indication of a contract of concession with estimated budget estimated at maximum average value of R$ 11.42 (eleven reais and forty two cents) per meal to be executed in the University Restaurant located in the University Center North of Espírito Santo to base a possible bidding process. Keywords: Restaurant. University Public. Outsourcing. Bidding.